Composición y distribución de hepáticas (Marchantiophyta) en un intervalo altitudinal en la Cordillera Oriental de Colombia - Cacua-Toledo, Cristhian Fernando (2018)
Composition and distribution of liverworts (Marchantiophyta) in a continuous altitudinal range on the Cordillera Oriental of Colombia. The species composition of liverworts varies with altitude in the Northern part of the Andes due to the relationship of biotic (vegetation) and abiotic factors (temperature, humidity, and sunlight brightness). In order to test this affirmation we determined the diversity, species composition, abundance, and distribution of species of Marchantiophyta in an altitudinal range from 2 400 to 3 400 m on the Colombian Cordillera Oriental, and established how these vary with altitude and life-zones, regarding abiotic factors. Samples, taken every 200 m in the altitudinal range, and environmental data were registered during a year. We found 162 species, the composition of liverworts varied throughout the altitudinal gradient with a high number of unique species in each altitude. The maximum diversity was found at 3 000 m, along with a dominance of leafy habit and epiphytic species, while the higher richness of families and genera was found between 3 200 and 3 400 m. Anoplolejeunea conferta had the largest value of coverage in the zone, the highest value of importance value index (IVI), and the widest altitudinal distribution, from 2 400 to 3 000 m in four different substrates. The liverworts were distributed differently with altitude, we found a high beta diversity (0.864) due to the replacement of species, with more that 30 % of dissimilarity in species composition every 200 altitudinal meters, mainly depending on sunlight brightness variation. Accordingly, we found that abiotic factors like temperature, humidity, and sunlight brightness and its relationship vegetation are determinant in the diversity and altitudinal distribution of liverworts in the study area. Rev. Biol. Trop. 66(2): 559-570. Epub 2018 June 01.